The inspection [videorecording (DVD)] - Bratton, Elegance; Pope, Jeremy; Castillo, Raul; Lombardi, McCaul; Dominguez, Aaron; Logan, Nicholas; Esfandi, Eman; Kai, Andrew; Joseph, Aubrey; Woodbine, Bokeem; Union, Gabrielle (Lionsgate, 2023)
In Elegance Bratton's deeply moving film inspired by his own story, a young, gay Black man, rejected by his mother and with few options for his future, decides to join the Marines, doing whatever it takes to succeed in a system that would cast him aside. But even as he battles deep-seated prejudice and the grueling routines of basic training, he finds unexpected camaraderie, strength, and support in this new community, giving him a hard-earned sense of belonging that will shape his identity and forever change his life.